EFL Teacher’s Classroom Language in Speaking Skill Enhancement: EFL Students’ Voices - Ana Safitri; Choiril Anwar (Journal of Advanced Multidisciplinary Research, 2021)
This study was about students’ perception toward the use of english teacher’s classroom language in speaking skill enhancement. The objective of this research was to find out the high school students’ perceptions toward the use of English teacher’s classroom language in speaking skill enhancement. This study used descriptive case study. The participants of this research were 36 students of class X MIPA 7 of SMA Negeri 11 Semarang. The instrument used in this study was an open ended questionnaire and closed-ended questionnaire. The results showed that students had positive perceptions about the use of English teacher's classroom language needed as the facilitator in the classroom in speaking skills enhancement. The student's opinion also said that when in the classroom, the teacher did not only use English as the classroom language, but mixed it with Indonesian so that students who were not fluent could follow the lesson well.